Gender Equality and Women Participation in Government: the case of Kazakhstan - A. A. Kireyeva; G. K. Kenzhegulova; Osama Rajkhan (Экономика: стратегия и практика)
Gender equality today is gaining all the relevance in the planning of the State program around the world. When planning government programs, they follow certain steps to achieve this goal. However, the goal of this system remains acute in many countries around the world. This article is devoted to the issue of gender policy in Kazakhstan. The article examined indicators such as women’s participation in leadership positions, employment in the labor market, education, the wage gap and how they participate in women’s participation in parliament. The participation of women in parliament was identified as one of the key factors in the development of gender equality. The article considered the theory of context. The results of the study confirmed the theory of context. To promote gender equality policies, the application of policies must be considered. The results showed that the wage gap and women’s participation in the labor market have a significant impact on women’s participation in parliament. The activity of women in education, that is, the increase in the number of women among students, however, did not have a significant impact on the participation of women in parliament. The SPSS program was used for the regression analysis. Also, a statistical analysis was carried out for a deeper study of the influence of factors on the activity of women in the state. The SPSS program was used for the regression analysis.